Teenage motherhood in Latin America and the Caribbean. Trends, problems and challenges - NU. CEPAL (ECLAC, 2014)
Teenage motherhood: pregnant with consequences.This issue sets out to show the situation of teenage pregnancy in the Latin American and Caribbean region. The central article draws attention to the persistently high levels of adolescent fertility, which are closely linked to conditions of increased poverty and vulnerability and lead to difficult situations for the young mother, her family and her offspring.